Mining spatio-temporal data of traffic accidents and spatial pattern visualization - Lavrač, Nada (Metodološki zvezki, 2008)
Spatial data mining is a research area concerned with the identification of interesting spatial patterns from data stored in spatial databases and geographic information systems (GIS). This paper addresses the analysis of spatial and time stamped data of Slovenian traffic accidents which, together with other GIS data, enabled the construction of spatial attributes and the creation of a time-stamped spatial database. This database was analyzed by means of basic descriptive statistical methods, an approach to short time series clustering, spatial clustering, as well as visualization using GIS and GoogleEarth facilities.
Keywords: geografski informacijski sistemi; prometne nesreče; podatkovno rudarjenje; časovne vrste; razvrščanje v skupine